ℂ-differentiability of mappings of Hilbert spaces - Gretskii, O. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The process of differentiation is studied for a class of mappings of regions of a Hilbert space. We introduce the concept of ℂCl-differentiability of a mapping at a point and establish sufficient conditions of ℂCl-differentiability.